2013
DOI: 10.1371/journal.pone.0066367
|View full text |Cite
|
Sign up to set email alerts
|

MRI Markers for Mild Cognitive Impairment: Comparisons between White Matter Integrity and Gray Matter Volume Measurements

Abstract: The aim of the study was to evaluate the value of assessing white matter integrity using diffusion tensor imaging (DTI) for classification of mild cognitive impairment (MCI) and prediction of cognitive impairments in comparison to brain atrophy measurements using structural MRI. Fifty-one patients with MCI and 66 cognitive normal controls (CN) underwent DTI and T1-weighted structural MRI. DTI measures included fractional anisotropy (FA) and radial diffusivity (DR) from 20 predetermined regions-of-interest (ROI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 76 publications
10
71
0
Order By: Relevance
“…Still, our results may provide a few clues to start deciphering these pathways. First, the strong relation of the MeDi with WM microstructure in extensive areas (with no specific involvement of tracts generally altered in AD, e.g., the cingulum and fornix) along with the absence of meaningful association with GM atrophy (specifically in AD regions, e.g., the hippocampus) suggests that mechanisms are not primarily related to AD neurodegeneration [35][36][37][38][39][40]. It remains possible that our study was underpowered to detect associations with volumes; however, we were able to detect the effect of age, suggesting sufficient power in this sample to capture wellestablished risk factors for brain atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Still, our results may provide a few clues to start deciphering these pathways. First, the strong relation of the MeDi with WM microstructure in extensive areas (with no specific involvement of tracts generally altered in AD, e.g., the cingulum and fornix) along with the absence of meaningful association with GM atrophy (specifically in AD regions, e.g., the hippocampus) suggests that mechanisms are not primarily related to AD neurodegeneration [35][36][37][38][39][40]. It remains possible that our study was underpowered to detect associations with volumes; however, we were able to detect the effect of age, suggesting sufficient power in this sample to capture wellestablished risk factors for brain atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Yamasue et al (2007) also reported significant correlations between somatic complaints in sarin attack victims and reduced FA in the temporal stem bilaterally (peak MNI coordinates: 34, 0, −15; −38, 2, −16), which corresponded to the bilateral uncinate fasciculus in the DTI atlas, and left subinsula (peak MNI coordinates: −28, −6, 8), which corresponded to the left external capsule in the DTI atlas. For each participant, we extracted the mean FA, axial and radial diffusivity value from each tract using a previously described method (Zhang et al, 2013). To protect against type I error, we reduced the number of measurements by averaging the DTI values from the left and right sagittal straitum and uncinate fasciculus to create one temporal stem ROI.…”
Section: Dti Image Processingmentioning
confidence: 99%
“…[19][20][21][22][23] Furthermore, evidence is accumulating that novel imaging techniques, such as diffusion tensor imaging (DTI), can detect subtle impairments in white matter tract integrity before they can be seen on conventional MRI, suggesting that WMHs represent only the extreme end of a continuous spectrum of white matter injury. 24,25 MRI also enables the measurement of progression of WMHs over time. [26][27][28] As regards the underlying pathology, there is little doubt that the majority of these lesions are ischaemic in origin.…”
Section: Introductionmentioning
confidence: 99%